MRI assessment of cerebral perfusion in clinical trials. Issue 4 (April 2023) - Wang, Xue; Bishop, Courtney; O'Callaghan, James; Gayhoor, Ali; Albani, Justin; Theriault, Wendy; Chappell, Michael; Golay, Xavier; Wang, Danny; Becerra, Lino
Highlights: Use of MRI perfusion imaging in clinical trials and as an alternative to other imaging modalities. Detailed description of imaging procedures, best practices in clinical trials. Review of currently available software, recommendations, and assessment of test re-test repeatability of ASL. Compiled references for further detailed description of the technique and applications beyond neuroimaging. Abstract : Neurodegenerative mechanisms affect the brain through a variety of processes that are reflected as changes in brain structure and physiology. Although some biomarkers for these changes are well established, others are at different stages of development for use in clinical trials. One of the most challenging biomarkers to harmonize for clinical trials is cerebral blood flow (CBF). There are several magnetic resonance imaging (MRI) methods for quantifying CBF without the use of contrast agents, in particular arterial spin labeling (ASL) perfusion MRI, which has been increasingly applied in clinical trials. In this review, we present ASL MRI techniques, including strategies for implementation across multiple imaging centers, levels of confidence in assessing disease progression and treatment effects, and details of image analysis.